Decoding Validity: Embodied Cognition in Shaping Concepts about Objectivity, Subjectivity, and Institutional Dynamics - Restrepo Rodas, Jonathan; Niño Buitrago, Laura; Suárez de La Torre, Mercedes (Íkala, Revista de Lenguaje y Cultura, 2025)
The notion of validity has been largely questioned in diverse research domains. While it has a long tradition in philosophy and logics, cognitive linguists are approaching new ways of understanding why it is possible to form representations in the mind that are framed in validity values, a cognitive aspect that is intertwined in the construction of concepts and reasoning. Ultimately, this impacts what humans validate and invalidate, accept as true or judge as false, and consider moral and immoral. The present article provides an approximation to a specific linguistic and cognitive process that is apparently in charge of validating and invalidating the concepts individuals create in the mind, with the aid of their socio-physical experience. Following an ethnomethodological research design, this article shows the compilation and analysis of participants’ ideas about harming or protecting the environment. The findings suggest that the embodied experience individuals create, particularly in terms of geometry, mathematics, and physics, plays a crucial role in validating and invalidating mental representations. This study sheds light on the intricate connections between socio-physical experiences and the construction of concepts, by providing valuable insights into the mechanisms underlying human cognition from language production.